Research on the Needs and Preferences of Elderly Consumers in Fashion Design - Zhao, Lujia (Advances in Humanities and Contemporary Studies, 2023)
By 2050, the world’s population aged 65 and above will reach 1.6 billion. The fashion market for elderly consumers has excellent potential, but there is a lack of research and design guidelines in this field. Previous research mainly focused on the functionality of clothing while neglecting the aesthetic and expressive factors in elderly clothing choices. This study aims to investigate the needs and preferences of elderly consumers in fashion design and propose design suggestions for elderly clothing by analyzing their needs and preferences to change the current situation of the elderly fashion market and make the creation of elderly dresses more humane. The FEA consumer needs model is an essential theoretical framework for guiding this study. This study used a mixed research method to interview four Chinese elderly consumers and collected 207 questionnaires for Chinese elderly consumers, using Thematic analysis, frequency analysis, and descriptive statistical analysis. The research reveals the different needs and preferences of elderly consumers in Fashion design. The research findings emphasize the importance of combining comfort and fashion in elderly fashion design while providing opportunities for self-expression. This study contributes to the existing literature on the needs and preferences of elderly consumers in fashion design. It provides practical solutions for designers to develop products that meet these needs and preferences. This study can potentially improve the quality of life of elderly consumers, increase sales in the elderly fashion market, and promote social inclusion, positively impacting the fashion industry and society.